Blood Donor Selection Profile an Important Tool for Blood Safety: An Institutional Experience - Shaan Khetrapal; Pushpa Bisht; Zeeba Shamim Jairajpuri; Safia Rana; Sujata Jetley (Archives of Medicine and Health Sciences)
Background and Aim: Blood transfusions can be a crucial, life-saving treatment in modern medical and surgical practice. The primary objective of blood transfusion services worldwide is to guarantee the availability of a sufficient and safe supply of blood and blood products. Meticulous donor screening and use of highly sensitive techniques for the detection of transfusion-transmitted infections (TTIs) may help reduce the risk of TTIs and, hence, are important steps to ensure safety for both donor and recipient. Materials and Methods: This is a retrospective record-based study done at Hamdard Institute of Medical Sciences and Research. The blood donors’ data from January 2012 to December 2022 (10 years) were collected from the blood bank registry at the study site and were analyzed. Results: Males dominated the donor population (98.2%) with females comprising only (1.8%). In total, 10.9% were found unfit for donation for various reasons. Voluntary donors were (6.3%) and replacement donors were (93.7%). Out of the reasons for deferral, majority 497/1223 (40.6%) donors were deferred due to hemoglobin <12.5 g/dl, followed by 156/1223 (12.8%) deferrals due to alcohol intake within the past 72 h. Conclusion: Safe donor selection is the first step toward safe transfusion services. Identification of population groups that can be targeted to enhance the pool of willing blood donors is made easier by studying and analyzing the blood donor profile.